Spatial and temporal coherence properties of single free-electron laser pulses - Singer, Andrej; Sorgenfrei, F.; Mancuso, A. P.; Gerasimova, N.; Yefanov, O. M.; Gulden, J.; Gorniak, Thomas; Senkbeil, Tobias; Sakdinawat, A.; Liu, Y.; Attwood, D.; Dziarzhytski, S.; et al. (Optics express, 2012)
The experimental characterization of the spatial and temporal coherence properties of the free-electron laser in Hamburg (FLASH) at a wavelength of 8.0 nm is presented. Double pinhole diffraction patterns of single femtosecond pulses focused to a size of about 10×10 μm2 were measured. A transverse coherence length of 6.2 ± 0.9 μm in the horizontal and 8.7 ± 1.0 μm in the vertical direction was determined from the most coherent pulses. Using a split and delay unit the coherence time of the pulses produced in the same operation conditions of FLASH was measured to be 1.75 ± 0.01 fs. From our experiment we estimated the degeneracy parameter of the FLASH beam to be on the order of 1010 to 1011, which exceeds the values of this parameter at any other source in the same energy range by many orders of magnitude.
Gesehen am 20.08.2019